PRAKTIK ECO-GREEN PROJECT MAHASISWA PROGRAM IISMA UGM DAN MAHASISWA UNWIDHA PEDULI TERHADAP LINGKUNGAN - Rachim, Annisa Fajrina; Widayanti, Sukasih Ratna; Santoso, Gunawan Budi; Hersulastuti; Purwanti, Titik; Setiyadi, D. B. P.; Pratono, Sigit Adhi; Hartanto; Tasari (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
This community service program is a series of activities that involves students and the academic community within the Faculty of Psychology, Gadjah Mada University, and some faculties in Widya Dharma Klaten University through an eco-green program for environmental care. The methods for implementing activities include as follows: 1) collecting data profiles on students and the academic community within Gadjah Mada University and Widya Dharma Klaten University and 2) empowering students through eco-green training on student empathy for the environment. The results of the activity obtained positive results where there was a change in student behavior before and after the activity. Developing a leadership spirit and cultivating students' sense of empathy for the environment through eco-green programs is not enough to be done in a short time, but requires a long and continuous period of time. Future activities need to continue to be carried out through several improvements in implementation methods.